2015
DOI: 10.7585/kjps.2015.19.3.248
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Uptake and Removal by Processing Types of Triazole Fungicides in Onion

Abstract: Uptake of the triazole fungicides, fluquinconazole and tetraconazole from shoot part of onion was assessed by determining residual amounts of applied fungicides in edible and shoot parts of onion after the foliar application. Combined product of fluquinconazole and tetraconazole (14:7, v/v) as a 21% active ingredient of suspended emulsion formulation was diluted at ratio of 500 and 200 times and sprayed on the shoot part of onion after sealing its root part with absorbent paper. At 10 days after the pesticide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The amount of chlorpyrifos absorbed in cucumber root was found to range from 1.0 to 1.3% of the initial soil concentration and was not translocated to fruits [11]. Studies with boscalid, chlorfenapyr, fluquinconazole, and tetraconazole found that the concentrations of these chemicals in Korean cabbage or onion were less than 2.5% compared with the initial soil concentration [25,26].…”
Section: Introductionmentioning
confidence: 94%
“…The amount of chlorpyrifos absorbed in cucumber root was found to range from 1.0 to 1.3% of the initial soil concentration and was not translocated to fruits [11]. Studies with boscalid, chlorfenapyr, fluquinconazole, and tetraconazole found that the concentrations of these chemicals in Korean cabbage or onion were less than 2.5% compared with the initial soil concentration [25,26].…”
Section: Introductionmentioning
confidence: 94%
“…Some experiments have analyzed the levels of pesticides absorbed from soil contaminated with boscalid, chlorfenapyr, fluquinconazole, and tetraconazole. These studies showed that the levels of these pesticides in Korean cabbage or onion were less than 2.5% in comparison to the spiked concentration in the soil [29,30].…”
Section: Introductionmentioning
confidence: 98%
“…Hence, pesticide residues present within plant tissues may not be easy to be removed using any of external treatment methods. Some studies showed that heating or frying food ingredients with water or oil could reduce significant amounts of pesticide residues [16,17]. However, as fruit crops like apples are routinely consumed in a fresh state, several limited methods such as washing and peeling can be employed for removing the pesticide residues [18].…”
Section: Introductionmentioning
confidence: 99%